1989
DOI: 10.1104/pp.89.3.768
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Soybean Somatic Embryos and the Transition to Plantlet Growth

Abstract: MATERIALS AND METHODS The maturation of soybean (Glycine max L. Merr.) somatic embryos was characterized. Maturation was assayed by evaluating the ability of somatic embryos to make the transition to a plantlet through a germination-like process. Somatic embryos were organized from cotyledons of immature soybean embryos. Maturation of somatic embryos occurred on a Murashige-Skoog basal medium supplemented with activated charcoal and 0.28 molar sucrose. After 8 weeks on this medium, somatfc embryos exhibited vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(66 citation statements)
references
References 28 publications
3
61
0
2
Order By: Relevance
“…Increased viability and germination frequency suggested that embryos treated with ABA are physiologically more mature. Maturation of somatic embryos is a process during which a large amount of nutrients accumulate (Buchheim et al 1989). ABA has been reported to stimulate protein accumulation of soybean zygotic embryos cultured in vitro during the early phase of embryogenesis (Ackerson 1984).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Increased viability and germination frequency suggested that embryos treated with ABA are physiologically more mature. Maturation of somatic embryos is a process during which a large amount of nutrients accumulate (Buchheim et al 1989). ABA has been reported to stimulate protein accumulation of soybean zygotic embryos cultured in vitro during the early phase of embryogenesis (Ackerson 1984).…”
Section: Resultsmentioning
confidence: 99%
“…After formation, somatic embryos require a long time (ca. 60 d) for growth, development and maturation (Buchheim et al 1989;Baily et al 1993a). The embryo germination frequency is also low (0-5%, Parrott et al 1988) and requires complex manipulations (Buchheim et al 1989;Baily et al 1993b).…”
Section: Mots Clés: Glycine Max Embryogenèse Somatique Culture In Vmentioning
confidence: 99%
See 2 more Smart Citations
“…35 Three and 4 hours desiccated calli reduced fresh weight due to reduction of water content and stimulated callus growth, globularization and embryo formation in 2 date palm cultivars. 31 Desiccation also has been reported to promote somatic embryo differentiation and development to other crops like as soybean, 36,37 wheat, 38 spruce 39 and cassava. 40 In recent years tissue culture techniques are being used as a useful tool to elucidate the mechanism involved in salt tolerance.…”
Section: Introductionmentioning
confidence: 99%